GAMBARAN BAURAN STRATEGI PUBLIC RELATIONS DALAM MENINGKATKAN CITRA POSITIF PADA PT KONE INDO ELEVATOR - Refiani Puspa Dewi; Geofakta Razali (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
The purpose of this study is to find out the description on the strategy mixture of public relations in increasing positive image and to find out what obstacles facing of PT. KONE Indo Elevator. This study used qualitative research method along with interview, observation, and documentation technic. This study used the theory of the seven strategy mixtures of public relations which are publication, event, news, relation to public, negotiation and lobbying technic, Corporate Social Responsibility (CSR), and company identity. The result of the conducted study shows that strategy mixture of public relations implemented by PT. KONE Indo Elevator works quite well. The effort is proven to be succeeded that there are still many people who put in their trust to choose and recommend KONE.